Insights into Membrane Damage by α-Helical and β-Sheet Peptides - Warin Rangubpit; Hannah E. Distaffen; Bradley L. Nilsson; Cristiano L. Dias (Biomolecules, 2025)
Peptide-induced disruption of lipid membranes is central to both amyloid diseases and the activity of antimicrobial peptides. Here, we combine all-atom molecular dynamics simulations with biophysical experiments to investigate how four amphipathic peptides interact with lipid bilayers. All peptides adsorb on the membrane surface. Peptide M01 [Ac-(FKFE)2-NH2] self-assembles into <semantics>β</semantics>-sheet nanofibrils that span both leaflets of the membrane, creating water-permeable channels. The other three peptides adopt <semantics>α</semantics>-helical structures at the water–lipid interface. Peptide M02 [Ac-FFKKFFEE-NH2], a sequence isomer of M01, does not form <semantics>β</semantics>-sheet aggregates and is too short to span the bilayer, resulting in no observable water permeation across the membrane. Peptides M03 and M04 are <semantics>α</semantics>-helical isomers long enough to span the bilayer, with a polar face that allows the penetration of water deep inside the membrane. For the M03 peptide [Ac-(FFKKFFEE)2-NH2], insertion into the bilayer starts with the nonpolar N-terminal amino acids penetrating the hydrophobic core of the bilayer, while electrostatic interactions hold negative residues at the C-terminus on the membrane surface. The M04 peptide, [Ac-FFKKFFEEFKKFFEEF-NH2], is made by relocating a single nonpolar residue from the central region of M03 to the C-terminus. This nonpolar residue becomes unfavorably exposed to the solvent upon insertion of the N-terminal region of the peptide into the membrane. Consequently, higher concentrations of M04 peptides are required to induce water permeation compared to M03. Overall, our comparative analysis reveals how subtle rearrangements of polar and nonpolar residues modulate peptide-induced water permeation. This provides mechanistic insights relevant to amyloid pathology and antimicrobial peptide design.